sodA modulates in vitro and in vivo virulence of Yersinia enterocolitica - Zhang, Yingying; Ma, Yan; Xia, Xiaodong; Li, Hao; Jin, Tong; Meng, Xinru; Liu, Xing; Yang, Xuan; Xie, Ruixue; Li, Li (Frontiers in Microbiology, 2025)
IntroductionYersinia enterocolitica is a significant foodborne Gram-negative pathogen causing gastroenteritis and systemic infections. Its virulence is attributed to its ability to withstand oxidative stress and evade host immunity. This study investigates the role of the sodA gene, which encodes manganese-dependent superoxide dismutase (Mn-SOD), in the pathogenicity of Y. enterocolitica.MethodsUsing sodA knockout (ΔsodA) and complemented (ΔsodAC) strains, we assessed bacterial adhesion and invasion in Caco-2 epithelial cells, intracellular survival in RAW264.7 macrophages, and colonization in BALB/c mice. Inflammatory responses were evaluated through histopathology, immunohistochemistry (NF-κB p65), and qRT-PCR analysis of cytokine expression.ResultsThe ΔsodA mutant exhibited significantly reduced adhesion to and invasion of epithelial cells, impaired survival within macrophages, and decreased colonization in murine ileum and colon tissues. Furthermore, ΔsodA infection resulted in attenuated inflammatory responses, evidenced by lower expression of IL-1β, TNF-α, and NF-κB p65. Functional restoration was observed in the complemented strain, confirming the specific role of sodA.DiscussionThese results demonstrate that sodA is essential for the full virulence of Y. enterocolitica, influencing oxidative stress resistance, host cell invasion, and modulation of immune responses. This study highlights sodA as a potential target for developing therapeutic strategies against Y. enterocolitica infections.